Enhancing Public Service Quality through Strategic Management at the Public Service Mall - Syah, Syahiruddin; Bastian, Bastian; Baharuddin, Aris (PINISI Discretion Review, 2025)
Efforts to improve public service are crucial for enhancing welfare, with one of the main focuses being in the field of public services. The Luwu Regency Government plays an important role in the delivery of these public services. This study aims to analyze the strategies for improving the quality of public services at the Public Service Mall (MPP) of Luwu Regency, with the hope of providing encouragement for the local government to continue improving the quality of services provided. This research uses a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The data obtained are then analyzed and contextualized with applicable standards in accordance with relevant literature studies. This research is located at the Investment and One-Stop Integrated Service Office, which is responsible for the operations of the MPP of Luwu Regency. The research findings indicate that there are five key aspects in the strategy to improve public service quality at the MPP of Luwu Regency. These five aspects are the core strategy, consequence strategy, customer strategy, monitoring strategy, and cultural strategy. The core strategy focuses on improving employee performance and providing adequate facilities and infrastructure. The consequence strategy emphasizes accountability and transparency through the implementation of e-government and community feedback mechanisms. The customer strategy aims to ensure excellent service by guaranteeing quality that meets public expectations. The monitoring strategy uses the Community Satisfaction Index (IKM) as the basis for evaluating and improving services. Finally, the cultural strategy emphasizes the adjustment of values and ethics in public service to align with the community's environmental conditions.